Intense Exercise Causing Central Retinal Vein Occlusion in a Young Patient: Case Report and Review of the Literature - Moisseiev, Elad; Sagiv, Oded; Lazar, Moshe (Case reports in ophthalmology, 2014)
We report a 19-year-old patient who developed a central retinal vein occlusion (CRVO) with significant macular edema and visual impairment following intense exercise and dehydration. The patient was treated with 3 intravitreal bevacizumab injections with complete resolution. A review of the literature on the cause and treatment for CRVO in young patients was performed, focusing on the role of intense exercise and dehydration as a rare pathogenesis mechanism of CRVO.